دور الأدلة المستمدة من مسرح الجريمة في الإثبات الجنائي - شيراز بوحديش (جامعة الوادي University of El Oued, 2025)
يعتبر مسرح الجريمة نقطة الإطلاق لأعمال التحقيق كونه المكان الذي يجمع كل الآثار المتعلقة بالجريمة أو أغلبها حيث يقوم بمعاينته عناصر الشرطة العلمية المكلفين بجمع الآثار والكشف عنها مهما كان نوعها مستعينين بالوسائل العلمية الحديثة والمتطورة ضمانا لصحة الإجراء وعدم اتلافها من أجل الاستفادة منها في كشف الحقيقة. وبعد فحص الأثر وتوضيح علاقته بأطراف الجريمة ليرتقي بعد ذلك لأن يكون دليلا، حيث يخضع لتقدير قاضي التحقيق الذي إن رآه يشكل جريمة أصدر أمرا بالإحالة على حسب نوعها سواء كانت جنحة أو مخالفة أو جناية، ثم تخضع هذه الأوامر إلى رقابة غرفة الاتهام التي لها صالحية تأييدها أو استئنافها في شكل قرارات قابلة للطعن، فإن احيل ملف الدعوى الى المحكمة المختصة بموجب قرار غرفة الاتهام، فإن أدلة مسرح الجريمة تخضع للسلطة التقديرية للقاضي كباقي الأدلة الأخرى، ويبني حكمه استنادا عليها وعمال بإقتناعه الشخصي ويتوجب عليه التسبيب في حكمه. The crime scene is considered the starting point for the investigation as it contains all the relevant evidence. The scientific police elements assigned to collect evidence and uncover its nature and significance attend the scene, regardless of the type of evidence, using modern scientific means to ensure its integrity and prevent any tampering in order to benefit from it in uncovering the truth. After examining the evidence and clarifying its relationship to the crime’s circumstances, a report is written. The investigating judge may then decide whether what he sees constitutes a criminal offense, issuing a referral order based on its nature, whether a felony, misdemeanor, or infraction. This order is subject to review by the Indictment Chamber, which has the authority to approve or overturn it in the form of appealable decisions. If the case is referred to the competent criminal court by the Indictment Chamber, the trial takes place in the presence of the judge, who bases his ruling on the evidence presented and the work of the judge, providing justification for his decision
جريمة وأمن
Keywords: مسرح الجريمة، الأدلة المادية، أثار مسرح الجريمة، التحقيق القضائي، السلطة التقديرية للقاضي.; crime scene; physical evidence; traces of the crime scene; judicial investigation; discretionary authority of the judge.